Concrete repair to EN 1504 diagnosis, design, principles and practice - Raupach, Michael; Büttner, Till (CRC Press, Taylor & Francis Group, 2014)
The Construction Sector Is Increasingly Focused On RepairAs concrete structures are maintained longer for both environmental and financial reasons, the diagnosis, design, and selection of products, and repair work all depend on the individual condition of the buildings and require specialist knowledge from everyone involved. Concrete Repair to EN 1504: Diagnosis, Design, Principles and Practice provides relevant background and practical guidance on concrete repair. This book is based on the new European Standard EN 1504, which is used as the actual basis for concrete repair works, in Europe and beyond.